Hypofractionated radiotherapy for renal cell carcinoma with inferior vena cava tumour thrombus - Bełdzińska, Karolina; Gądek, Konrad; Rutkowski, Jacek (Contemporary Oncology/Współczesna Onkologia, 2022)
Renal cell carcinoma (RCC) constitutes about 3% of all malignant neoplasms in adults. Clear cell carcinoma is the most frequent type, accounting for about 65% of cases. It tends to invade the veins and form tumour thrombi in inferior vena cava (IVC-TT), occasionally reaching the right atrium. Nephrectomy and thrombectomy are standard therapeutic procedures performed in RCC-IVC-TT. Despite proven effectiveness of surgery, this entity in IVC-TT is associated with poor outcome. The role of palliative radiotherapy in this entity is undetermined. We present a case of a 43-year-old female patient after right-sided nephrectomy due to advanced RCC which invaded the IVC, hepatic veins, and right atrium. The patient has been treated with postoperative, hypofractionated radiotherapy on the residual disease.